Redefinition of the vittata species group of Epicauta Dejean (1834) (Coleoptera: Meloidae) and taxonomic revision of the species from southern South America - Campos-Soldini, María Paula; Roig-Juñent, Sergio Alberto (Zootaxa, 2011)
The Epicauta vittata group are commonly known as striped blister beetles and was defined by previous authors to include 32 species, 18 from North America, Central America and northern South America, and 14 from southern South America. In the present revision we revised 22 species from South America, excluding the following southern South American species: E. borgmeieri Denier, 1935; E. floydwerneri Martínez, 1955; E. franciscana Denier, 1935; E. fulginosa (Oliver, 1795); E. purpureiceps (Berg, 1889); E. rutilifrons Borchmann, 1930; and E. zebra (Dohrn, 1876) because they do not have the diagnostic characters of the group. The species of the E. vittata group from southern South America are: E. bosqi Denier, 1935; E. clericalis (Berg, 1881); E. grammica (Fischer, 1827); E. leopardina (Haag-Rutemberg, 1880); E. luteolineata Pic, 1933; E. missionum (Berg, 1881); E. monachica (Berg, 1883); E. rutilifrons Borchmann, 1930; plus two more species E. excavata (Klug, 1825); and E. semivittata (Fairmaire, 1875) until now not included in other groups. We provide a complete diagnosis of the E. vittata group from southern South America, redescribing and illustrating all included species. Detailed descriptions and illustrations of female and male genitalia are presented for the first time for these species. Finally, we provide an identification key for the ten species presently included in the E. vittata group, and update the geographic distribution of each species.